Case Report: Necrotizing Stomatitis as a Manifestation of COVID-19-Associated Vasculopathy - Emeršič, Nina; Tomaževič, Tanja; Točkova, Olga; Kopač, Matjaž; Volavšek, Metka; Ključevšek, Damjana; Avčin, Tadej (Frontiers in Pediatrics, 2021)
Necrotizing stomatitis is a rare, acute-onset disease that is usually associated with severely malnourished children or diminished systemic resistance. We describe a 1-year-old girl who developed necrotizing stomatitis, vasculitic rash, skin desquamation on the fingers and toes, and persistent hypertension after serologically confirmed SARS-CoV-2 infection. Her laboratory investigations revealed positive IgG anticardiolipin and IgG anti-β2 glycoprotein antibodies, and biopsy of the mucosa of the lower jaw showed necrosis and endothelial damage with mural thrombi. Swollen endothelial cells of small veins in the upper dermis were confirmed also by electron microscopy. As illustrated by our case, necrotizing stomatitis may develop as a rare complication associated with SARS-CoV-2 infection and can be considered as a part of the clinical spectrum of COVID-19 vasculopathy. The pathogenic mechanism could involve a consequence of inflammatory events with vasculopathy, hypercoagulability, and damage of endothelial cells as a response to SARS-CoV-2 infection.